Pocket Book to Enhance Knowledge and Attitude Regarding Prevention of Soil-transmitted Helmint - Liena Sofiana; Suci Musvita Ayu (International Journal of Evaluation and Research in Education (IJERE), 2017)
Indonesia, being a tropical area with high humidity, is a source of proliferation of worms. Soil-Transmitted Helminths infection is widespread in all rural and urban areas. Children who are infected usually experience lethargy, pallor or anemia, weight loss and listlessness, as well as decreasing their learning concentration and productivity. Prevention effort to reduce the incidence of Soil-Transmitted Helminths infection is conducted by providing the information on Soil-Transmitted Helminths infection. Health promotion cannot be separated from media because messages delivered through media can be more interesting and easier to understand. The purpose of this study is to determine the effectiveness of a pocket book to increase preventive behavior for Soil-Transmitted Helminthes Infections. This type of research was a quasi-experimental study. The samples of this study were all elementary school infected students in grades 3, 4, and 5 with a package of interventions for the provision of a pocket book. The effectiveness of the pocket book is determined by using the t test. There are differences between the mean of knowledge and attitude, but the mean of behavior of Soil -Transmitted Helminths Infection before and after the pocket book is similar.